(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
With the aim of enhancing speed and accuracy for intricate surgical procedures, craniomaxillofacial surgeons have just begun using virtual surgical planning (VSP). Among its several uses, VSP has the potential to cure orbital fractures and other craniofacial abnormalities that might be either present at birth or developed over time. By illuminating the interplay between bone and neurovascular components, VSP helps the surgeon make sense of the craniofacial region’s intricate anatomy. In this particular example, the patient suffered from pan facial trauma and had several facial bone fractures. In order to prepare for the operation, the surgeon used an AM medical model to customize the micro plates. In order to improve the results of complicated procedures, this article also discusses the significance of AM medical models.